2017
DOI: 10.1016/j.jmathb.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Proof validation and modification in secondary school geometry

Abstract: Proof validation is important in school mathematics because it can provide a basis upon which to critique mathematical arguments. While there has been some previous research on proof validation, the need for studies with school students is pressing. For this paper, we focus on proof validation and modification during secondary school geometry. For that purpose, we employ Lakatos' notion of local counterexample that rejects a specific step in a proof. By using Toulmin's framework to analyze data from a task-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…Hence, in the same way as in Lakatos's research, it is important to develop tasks whose conditions are purposefully implicit so that students can avail themselves of, and consider, particular proofs and counterexamples. This is supported by our previous studies demonstrating that specific tasks, in the form of proof problems with diagrams that include hidden conditions, are helpful for students to explore proofs and counterexamples in secondary school geometry (Komatsu, 2017;Komatsu et al, 2017).…”
Section: Towards a Set Of Task Design Principlessupporting
confidence: 62%
See 3 more Smart Citations
“…Hence, in the same way as in Lakatos's research, it is important to develop tasks whose conditions are purposefully implicit so that students can avail themselves of, and consider, particular proofs and counterexamples. This is supported by our previous studies demonstrating that specific tasks, in the form of proof problems with diagrams that include hidden conditions, are helpful for students to explore proofs and counterexamples in secondary school geometry (Komatsu, 2017;Komatsu et al, 2017).…”
Section: Towards a Set Of Task Design Principlessupporting
confidence: 62%
“…This task condition led the students to proof construction for the given diagram and enabled them to produce the six types of diagrams, which had the potential to refute their conjecture, with the help of the dragging function of the DGE in Task 1-2. In our previous study (Komatsu et al, 2017), conversely, many secondary school students were found to encounter difficulties drawing diagrams that refuted their proofs in paper-and-pencil environments. The tasks used in that study were more difficult than those in case 1; nevertheless, without the use of dragging it would have been challenging for the three students in case 1 to produce various diagrams different from the one given in the original problem and thus to tackle their task also.…”
Section: Analysis Of Casementioning
confidence: 80%
See 2 more Smart Citations
“…En el campo de la enseñanza-aprendizaje de la matemática se han desarrollado trabajos relativos a la formulación de conjeturas y al empleo del contraejemplo para el tratamiento de conceptos, propiedades y relaciones matemáticas. En particular, en las investigaciones reportadas por Weber (2009), Komatsu (2010), Knuth y Ko(2013), Giannakoulias, Mastorides, Potari y Zachariades, (2010), Komatsu, Jones, Ikeda y Narazaki (2017), García y Morales (2013), Klymchuk, (2010), Zazkis y Chernoff (2008), Huang (2014) se han identificado que las mismas van dirigidas a profesores y estudiantes, en cada una de ellas se pone de manifiesto que la elaboración y utilización del contraejemplo es una herramienta didáctica para favorecer los procesos de validación y comprensión del conocimiento matemático.…”
Section: Introductionunclassified